Mental health problems of undocumented migrants in the Netherlands: A qualitative exploration of recognition, recording, and treatment by general practitioners - Teunissen, Erik; Van Bavel, Eric; Van Den Driessen Mareeuw, Francine; Macfarlane, Anne; Van Weel-Baumgarten, Evelyn; Van Den Muijsenbergh, Maria; Van Weel, Chris (Scandinavian journal of primary health care, 2015)
Objective. To explore the views and experiences of general practitioners (GPs) in relation to recognition, recording, and treatment of mental health problems of undocumented migrants (UMs), and to gain insight in the reasons for under-registration of mental health problems in the electronic medical records. Design. Qualitative study design with semi-structured interviews using a topic guide. Subjects and setting. Sixteen GPs in the Netherlands with clinical expertise in the care of UMs. Results. GPs recognized many mental health problems in UMs. Barriers that prevented them from recording these problems and from delivering appropriate care were their low consultation rates, physical presentation of mental health problems, high number of other problems, the UM's lack of trust towards health care professionals, and cultural differences in health beliefs and language barriers. Referrals to mental health care organizations were often seen as problematic by GPs. To overcome these barriers, GPs provided personalized care as far as possible, referred to other primary care professionals such as social workers or mental health care nurses in their practice, and were a little less restrictive in prescribing psychotropics than guidelines recommended. Conclusions. GPs experienced a variety of barriers in engaging with UMs when identifying or suspecting mental health problems. This explains why there is a gap between the high recognition of mental health problems and the low recording of these problems in general practice files. It is recommended that GPs address mental health problems more actively, strive for continuity of care in order to gain trust of the UMs, and look for opportunities to provide mental care that is accessible and acceptable for UMs.